(untitled) (Notes in Current Biology, 2018)
Since verbal working memory is more safe with traumatic brain injuries (TBI) than visual working memory (VWM), the purpose of the study was to determine the features of interregional interaction in the brain of military men with TBI who took part in the operations in the east of Ukraine, after that – military men with TBI. This study conducted on 16 male volunteers, right-handers, at the age of 18–21 years, who have no problems with their health – students of Taras Shevchenko National University of Kyiv (control group) and 16 male volunteers, right-handers, aged 27–43 – the patients of the Yu. I. Kundiyeva Institute for occupation health NAMS of Ukraine, Kyiv. During testing of VWM it was found that the reaction time in a military men group of with TBI was significantly higher than in the control group, although no significant differences were found between the relative numbers of errors. During VWM testing in the group of military men with TBI an interhemisphere relationship was detected in the somatosensory cortex, while in the control group a complicated fronto-parietal system of interhemisphere interactions was discovered. In the group of military men with TBI higher activity was detected not in the front-parietal system of top-down control of VWM, but in parietal and occipital zones. It should be noted that in the parietal-occipital network of VMW the bottom-up control processes more involved. It can be assumed that in the group of military men with TBI in the processes of visual memory the absence of complicated fronto-parietal system was compensated by more effective inclusion of cortical brain regions. This part of the brain is associated with the verbal processes of semantic analysis of visual information, which came mainly from its dorsal path. Instead of a higher level of control over coding, retention, and recovery of information from the frontal cortex as in control group, control of the processes of VWM may take the higher associative parietal cortex areas that are more based on the search for both new and already familiar stimulus by their features.